2022
DOI: 10.3390/ph15070833
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan-Mediated Inhibition of Fibrotic Properties in Oral Submucous Fibrosis via the MEG3/miR-181a/Egr1 Axis

Abstract: Oral submucous fibrosis (OSF) is a chronic fibrotic remodeling disease that can progress to oral cancer. However, efficient clinical diagnosis and treatment methods for OSF are still lacking. This study investigated the anti-fibrotic effect of fucoidan on oral fibrosis. To evaluate the fibrotic ability (myofibroblast activities), we performed wound-healing, Transwell migration, and collagen contraction assays by using patient-derived normal and fibrotic buccal submucous fibroblasts (BMFs and fBMFs, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“… 36 Therefore, in this study, we only stimulated BMFs with arecoline for 24 h, which has been reported in our previous studies to be sufficient for inducing the pro-fibrogenic phenotypes, such as increased α-SMA expression and collagen gel contraction ability. 30 , 37 Moreover, the arecoline-induced transcriptome profile of BMFs reported in a recent study supports our findings, indicating that low-dose arecoline-induced differentially expressed genes in BMFs were involved in ECM remodeling. 32 However, this is a relatively short duration compared to the OSF pathogenesis progression that may not reflect the potential long-term consequences of arecoline.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 36 Therefore, in this study, we only stimulated BMFs with arecoline for 24 h, which has been reported in our previous studies to be sufficient for inducing the pro-fibrogenic phenotypes, such as increased α-SMA expression and collagen gel contraction ability. 30 , 37 Moreover, the arecoline-induced transcriptome profile of BMFs reported in a recent study supports our findings, indicating that low-dose arecoline-induced differentially expressed genes in BMFs were involved in ECM remodeling. 32 However, this is a relatively short duration compared to the OSF pathogenesis progression that may not reflect the potential long-term consequences of arecoline.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study found a significant role of early growth response protein 1 (Egr-1) in promoting OSF progression. 30 The Egr-1 overexpression was controlled by non-coding mediated epigenetics regulation, promoting pro-fibrogenic properties and resulting in the fibroblast-to-myofibroblasts transformation. Consistent with our works, Li et al.…”
Section: Discussionmentioning
confidence: 99%
“… 6 At present, there is a lack of effective clinical diagnosis and treatment of OSF, most of which focus on reducing inflammation and improving oral opening to improve patients’ quality of life. 7 The expression of Notch was significantly upregulated in OSF tissues and TGF-β1-induced buccal mucosal fibroblasts. 8 NOTCH1 was identified as an independent prognostic factor for overall survival of early oral squamous cell carcinoma (OSCC).…”
Section: Introductionmentioning
confidence: 93%
“…LincRoR has been shown to modulate cancer progression via interaction with microRNA-145 [ 47 ], and microRNA-145-5p was shown to ameliorate hypertrophic scar through suppression of myofibroblast activation and reduction of Smad2/3 [ 53 ]. Furthermore, microRNA-181a has been demonstrated as an anti-fibrotic factor in fBMFs [ 54 ], and participated in TGF-β-induced EMT in hepatocytes [ 55 ]. As for miR-205, it was found to attenuate the angiotensin II-induced fibrosis in vivo and myofibroblast activation in atrial fibroblasts [ 56 ].…”
Section: Discussionmentioning
confidence: 99%